2023
DOI: 10.7759/cureus.33926
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Attitude Toward Disaster Preparedness Among Secondary School Students in the Western Region of Saudi Arabia

Abstract: BackgroundDisaster is any unexpected event that leads to significant harm exceeding the capacity of the affected community for coping. Unfortunately, disasters have increased during the last few years globally. Knowledge and attitude of people are the main steps for the success of disaster preparedness and management. Thus, this study was conducted to assess the level of knowledge and attitude about disaster preparedness among secondary school students in the western region of Kingdom of Saudi Arabia. Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As studies indicate, preparedness comes with higher knowledge and skills, which in turn help to cope with disasters ( 26 ). Trained volunteers can prove beneficial by transferring knowledge and experiences to local communities and improving public awareness concerning the management of various crises or disasters ( 27 ). Raising awareness and knowledge among volunteers improves their attitudes at times of crisis too ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…As studies indicate, preparedness comes with higher knowledge and skills, which in turn help to cope with disasters ( 26 ). Trained volunteers can prove beneficial by transferring knowledge and experiences to local communities and improving public awareness concerning the management of various crises or disasters ( 27 ). Raising awareness and knowledge among volunteers improves their attitudes at times of crisis too ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Or because it is not possible to conduct practical training due to the conditions of overcrowded classes, the crowded study schedule, the division of the school day into two periods, morning and evening, in addition to the fact that the evacuation plan needs to be prepared in advance in a deliberate manner. Divergent results were reported by Alkalash et al (2023) who found that 53.9% of the secondary school students had a good level of knowledge, and 95.9% of them showed a positive attitude toward disaster preparedness. Considering students' training on evacuation process (evacuation drills), slightly less than one third of students confessed that their schools did not train them.…”
Section: Aim Of the Studymentioning
confidence: 94%
“…In the same vein, study conduct in Kenya (Japheth, 2019) disclosed that 79.6% of secondary students confessed that their schools did not carry out fire safety. Likewise, Saudi study by Alkalash et al (2023) clarified that only 34.2% were already involved in a disaster drills or workshops in the school or city. Correspondingly, Musigapong and Phanprasit (2013), indicated that in their study only 18.8% of students who had practiced fire evacuation.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…2. Knowledge about disaster preparedness: The questionnaire was (16 items) adapted from Alkalash et al11 "yes or no"…”
mentioning
confidence: 99%